The validity of the Okun’s law: an empirical investigation for the Greek economy - Rigas, John; Theodosiou, Giorgos; Rigas, Nikolas; Blanas, George (TNEU, 2011)
The main objective of this study is to evaluate the relationship of Okun’s law for the Greek economy over the period 1960–2007. The results of the analysis using the model of the «first differences» showed an inverse relationship between unemployment and GDP. However, the quantitative value of the Okun’s law coefficient and the form of this relationship in the case of Greece is quite different from those estimated for other EU countries. This is partially explained by disparities between productivity growth rates in Greece and other EU countries [France and Spain]. Moreover, structural change tests conducted by using dummy variables indicated that the Okun’s coefficient for Greece for the period from 1980 to 2007 is different from that estimated for the period 1960–1980. Finally, for VAR order k = 2, the pairwise Granger causality tests showed that LNGDP Granger causes UN.
Keywords: Okun’s law; unemployment rate; stationarity; cointegration; causality